2004
DOI: 10.1007/1-4020-7862-5_4
|View full text |Cite
|
Sign up to set email alerts
|

Co-Ordination of E-Government

Abstract: Abstract:E-government is a move towards more use of networked information technologies in governments' services to citizens and companies. There will be strong expectations that these services are well co-ordinated and interoperable with the applications of citizens and companies. IT co-ordination is difficult, expensive and risk prone. The wide range of products and services in government makes co-ordination even harder. Co-ordination of egovernment should therefore be carefully prioritised and the ambitions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…As a result of this study, it was suggested that the leadership of the supreme leader is the most important factor for the success of the e-Government. Since then, many studies have emphasized the strong leadership of top leaders as a requirement for the success of e-Government and digital government [56][57][58]. However, in Korea, the political aspect inherent in digital government implementation was more important than these leadership factors.…”
Section: Political Characteristics Of Digital Government: As a Presid...mentioning
confidence: 99%
“…As a result of this study, it was suggested that the leadership of the supreme leader is the most important factor for the success of the e-Government. Since then, many studies have emphasized the strong leadership of top leaders as a requirement for the success of e-Government and digital government [56][57][58]. However, in Korea, the political aspect inherent in digital government implementation was more important than these leadership factors.…”
Section: Political Characteristics Of Digital Government: As a Presid...mentioning
confidence: 99%
“…Finally, Sørgaard (2003) notes that ambitions for e-government "are often unrealistic, and that political goals seem to dominate over effective, stepwise approaches to coordination. On a pragmatic level, there is a need to focus on simpler, process-oriented mechanisms for coordination ..." In other words, whether or not e-government seems an attractive banner to march under, the real progress will occur through analyzing and improving specific work systems that span organizations.…”
Section: It Innovations Related To Interorganizational Systems or Egomentioning
confidence: 99%
“…(cited by Sørgaard, 2003) If a work system's technology can be viewed as an actor and the infrastructure that supports it can be viewed as an actor, it is possible that an entire work system and its specific elements such as work practices, information, and products and services can be viewed as actors in the actornetwork. Further, the principle of alignment says that these elements change over time (through the planned and unplanned change in Figure 2) in order to remain aligned internally and externally.…”
Section: Comparison With Actor Network Theorymentioning
confidence: 99%